FISH YIELD FROM ASSAM PONDS KEPT UNDER DIFFERENT EXPERIMENTAL CONDITIONS - Parameswaran, S; Radhakrishnan, S; Selvaraj, C; Bhuyan, B R (Indian Journal of Fisheries, 2011)
Experiments conducted in ponds in Sibsagar, Assam, indicated that by liming, fertilization and artificial feeding, over six times the natural production of fish can profitably be obtained. Fertilization of limed ponds with cow dung and N-P-K was found to be more economical than fertilization of feeding with mustard oil-cake. A combination of Catla catla, Labeo rohita and Cirrhinus mrigala gave better yields when oil-cake was applied as fertilizer whilst C. catla, L. rohita and Cyprinus carpio var. communis combination yielded better when the same was given as alternate day feed. Catla showed the maximum growth potential among all the four species of carps. Scale carp grew faster than mrigal under comparable conditions. Unlike that of scale carp, the growth rate of catla, rohu and mrigal retarded during the winter months.